An efficient ATM voice service with flexible jitter and delay guarantees. - Le Pocher, H.
A transmission and multiplexing strategy appropriate for voice over asynchronous transfer mode (ATM), called delayed frame queueing (DFQ), is proposed. This frame-based strategy has features in common with the synchronous transfer mode and is thus well suited to service synchronous applications such as voice, while retaining the statistical multiplexing capabilities of ATM. In particular, the DFQ service discipline can provide explicit and nontrivial bounds for queue delay and jitter, for both bursty as well as continuous traffic streams. Furthermore, the DFQ discipline can combine a wide range of delay and jitter bounds while also managing the distribution of quality of service violations among the traffic streams when congestion occurs. Jitter control is performed at the network periphery and thus does not negatively influence multiplexing gain at intermediate nodes. This efficient strategy has major implications in terms of the preferred alternatives chosen by clients when implementing source clock recovery for voice. DFQ allows the entire range of implementation alternatives for voice over ATM to be appropriately serviced, such as ATM adaptation layer types 1 and 2 (AAL1/2), adaptive playout, and immediate playout
Keywords: AAL1.; AAL2.; ATM adaptation layer; DFQ service discipline; QoS; Adaptive playout; Asynchronous transfer mode; Bursty traffic streams; Congestion control; Continuous traffic streams; Delay guarantee; Delayed frame queueing; Efficient ATM voice service; Explicit bounds; Immediate playout; Jitter control; Jitter guarantee; Multiplexing gain; Nontrivial bounds; Quality of service; Queue delay; Source clock recovery; Statistical multiplexing; Transmission; Voice over ATM